Kualitas Organoleptik dan Nilai pH Kulit Kopi yang Difermentasi dengan Penambahan Level Trichoderma sp. yang Berbeda - Hasan Basri; Ach Syamsuddin; Dewi Ratih Ayu Daning (Politeknik Negeri Jember, 2019)
This study aimed to determine the quality of organoleptic and pH value of fermented coffee peel using Trichoderma sp. at different levels. The treatment of coffee peel fermented using Trichoderma sp. consisted of P0 (without Trichoderma sp.), P1 (7.5 g), P2 (15.0 g), and P3 (22.5 g). Each treatment consisted of 4 replications. The parameters observed included: organoleptic quality (color, aroma, and texture) and pH value. The organoleptic test using the scoring method by 12 panelists. The result was analyzed by analysis of variance (ANOVA). A comparison among different treatments was performed by Duncan Multiple Range Test (DMRT). Fermentation of coffee peel waste with Trichoderma sp. produces average light brown color, sour aroma, and softer texture with an increasing percentage of Trichoderma sp. The pH value of coffee peel fermentation with Trichoderma sp. ranged around 6.